Changes in DNA 5-Hydroxymethylcytosine Levels and the Underlying Mechanism in Non-functioning Pituitary Adenomas - Xu, Yiwen; Niu, Yamei; Deng, Kan; Pan, Hui; Feng, Feng; Gong, Fengying; Tong, Wei-Min; Chen, Shi; Lu, Lin; Wang, Renzhi; You, Hui; Yao, Yong; et al. (Frontiers in Endocrinology, 2020)
Epigenetic factors have been proven to contribute to pituitary adenoma formation. 5-hydroxymethylcytosine (5hmC), which is catalyzed by ten-eleven translocation 2 (TET2), is related to DNA demethylation. In order to explore the pathogenesis of nonfunctioning pituitary adenomas (NFPAs), we detected genomic 5hmC levels in 57 NFPAs and 5 normal pituitary glands, and TET2 expression, distribution and TET2 alteration. Genomic 5hmC levels in NFPAs were significantly lower than those in normal pituitary glands (0.38‰ (0.13~1.23‰) vs 2.47‰ (0.82~2.86‰), P<0.0001). There was medium positive correlation of 5hmC levels with TET2 total and nuclear expression in NFPAs (r=0.461, P=0.018; r=0.458, P=0.019). Genomic 5hmC levels in NFPAs with TET2 p.P29R were significantly decreased compared with those in wild type NFPAs (0.33±0.18‰ vs 0.51±0.25‰, P=0.021). We firstly found that genomic 5hmC loss was present in human NFPAs. Genomic 5hmC levels may be affected by TET2 expression, subcellular localization and TET2 mutation.